2018
DOI: 10.1016/j.jsxm.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Suprapubic Lipectomy and Penile Prosthesis Implantation

Abstract: Introduction A shorter penis is a frequent complaint following penile prosthesis implantation (PPI), and a large redundant suprapubic fat pad can conceal the penis and possibly compromise patient and partner satisfaction with length. Aim To evaluate feasibility and outcome of same-session, same-incision, PPI and suprapubic lipectomy (SPL). Methods In 22 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In those patients, we have become increasingly adept at removing this fat and exposing more penis at the time of penile prosthesis surgery. As others have noted, this can all be achieved through a single incision when the penile implant is placed through the dorsum rather than two incisions if the device were placed through a penoscrotal incision ( 25 , 26 ). In this surgery, a large elliptical shaped area of dystrophic suprapubic fat is removed and the resulting defect is then closed in multiple layers to create a single transverse incision as shown in a video and initial series that was recently published ( 27 ).…”
Section: Tips and Pearlsmentioning
confidence: 99%
“…In those patients, we have become increasingly adept at removing this fat and exposing more penis at the time of penile prosthesis surgery. As others have noted, this can all be achieved through a single incision when the penile implant is placed through the dorsum rather than two incisions if the device were placed through a penoscrotal incision ( 25 , 26 ). In this surgery, a large elliptical shaped area of dystrophic suprapubic fat is removed and the resulting defect is then closed in multiple layers to create a single transverse incision as shown in a video and initial series that was recently published ( 27 ).…”
Section: Tips and Pearlsmentioning
confidence: 99%
“…Lately, Hakky et al reported a technique that included panniculectomy with suction-assisted lipectomy and anchoring of herniated pubic skin to the abdominal wall (31). Most recently, two studies; Shaeer et al and Shah et al described the technique of the suprapubic lipectomy that can be utilized simultaneously with PP surgery with good postoperative outcomes (Figure 3G,H,I) (32,33).…”
Section: Suprapubic Lipectomymentioning
confidence: 99%